Question
\( \frac { - 4 \pm \sqrt { 4 ^ { 2 } - 4 \cdot 1 - 3 } } { 2 \cdot 1 } \)
Ask by Warner Simpson. in Argentina
Feb 04,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
Las soluciones son \( x = -\frac{1}{2} \) y \( x = -\frac{7}{2} \).
Solution
Claro, evaluemos la expresión paso a paso:
\[
\frac{ -4 \pm \sqrt{4^{2} - 4 \cdot 1 - 3 } }{2 \cdot 1}
\]
1. **Calcular el contenido de la raíz cuadrada:**
\[
4^{2} - 4 \cdot 1 - 3 = 16 - 4 - 3 = 9
\]
2. **Sustituir el valor de la raíz en la expresión original:**
\[
\frac{ -4 \pm \sqrt{9} }{2} = \frac{ -4 \pm 3 }{2}
\]
3. **Resolver para las dos posibles soluciones:**
- **Primera solución (+):**
\[
\frac{ -4 + 3 }{2} = \frac{ -1 }{2} = -\frac{1}{2}
\]
- **Segunda solución (-):**
\[
\frac{ -4 - 3 }{2} = \frac{ -7 }{2} = -\frac{7}{2}
\]
**Por lo tanto, las soluciones de la expresión son:**
\[
x = -\frac{1}{2} \quad \text{y} \quad x = -\frac{7}{2}
\]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
Let's break down this expression step by step. The expression inside the square root is calculated first: \( 4^2 - 4 \cdot 1 - 3 = 16 - 4 - 3 = 9 \). Now, substituting that back into the formula gives us: \( \frac{-4 \pm \sqrt{9}}{2 \cdot 1} = \frac{-4 \pm 3}{2} \). Now we have two possibilities: 1. For \( -4 + 3 \): \( \frac{-1}{2} \). 2. For \( -4 - 3 \): \( \frac{-7}{2} \). Thus, the solutions to the expression are \( -\frac{1}{2} \) and \( -\frac{7}{2} \).